(Bīt Ninurta = Beth Horon. On the History of the Kingdom of the Jerusalem in the Amarna Period) - Kallai, z.
קלאי. זכריה ותדמור, הייט, ביחדנינירתה בית-חורון. לקורות ממלכת ירושלים בתקופת אל־עמארנה ; Engl. summary; to EA 290.